Engaging children in the development of obesity interventions: exploring outcomes that matter most among obesity positive outliers - Sharifi, Mona (Patient Educ Couns, 2015)
OBJECTIVE: To explore outcomes and measures of success that matter most to 'positive outlier' children who improved their body mass index (BMI) despite living in obesogenic neighborhoods. METHODS: We collected residential address and longitudinal height/weight data from electronic health records of 22,657 children ages 6–12 years in Massachusetts. We defined obesity “hotspots” as zip codes where >15% of children had a BMI ≥95th percentile. Using linear mixed effects models, we generated a BMI z-score slope for each child with a history of obesity. We recruited 10–12 year-olds with negative slopes living in hotspots for focus groups. We analyzed group transcripts and discussed emerging themes in iterative meetings using an immersion/crystallization approach. RESULTS: We reached thematic saturation after 4 focus groups with 21 children. Children identified bullying and negative peer comparisons related to physical appearance, clothing size, and athletic ability as motivating them to achieve a healthier weight, and they measured success as improvement in these domains. Positive relationships with friends and family facilitated both behavior change initiation and maintenance. CONCLUSIONS: The perspectives of positive outlier children can provide insight into children’s motivations leading to successful obesity management. Practice implications: Child/family engagement should guide the development of patient-centered obesity interventions.